Firm expectations and news: Micro v macro - Benjamin Born; Zeno Enders; Manuel Menkhoff; Gernot J. Müller; Knut Niemann (Humboldt University Berlin, 2023)
Using firm-level data, we study how firm expectations adjust to news while accounting for a) the heterogeneity of news and b) the heterogeneity of firms. We classify news as either micro or macro, that is, information about firm-specific developments or information about the aggregate economy. Survey data for German and Italian firms allows us to reject rational expectations: Both types of news predict forecast errors at the firm level. Yet while firm expectations overreact to micro news, they underreact to macro news. We propose a general-equilibrium model where firms suffer from 'island illusion' to explain these patterns in the data.
urn:nbn:de:kobv:11-110-18452/27597-3
Keywords: D84; C53; E71; 330; Survey data; salience; overreaction; underreaction; micro news; macro news; island illusion; business cycle